2022
DOI: 10.1021/acsami.1c24306
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Spectrally Flat Infrared Photodetection with Thickness-Controlled Nanocrystalline Graphite

Abstract: Graphene, a zero-gap semiconductor, absorbs 2.3% of incident photons in a wide wavelength range as a free-standing monolayer, whereas 50% is expected for ∼90 layers. Adjusting the layer number allows the tailoring of the photoresponse; however, controlling the thickness of multilayer graphene remains challenging on the wafer scale. Nanocrystalline graphene or graphite (NCG) can instead be grown with controlled thickness. We have fabricated photodetectors from NCG that are spectrally flat in the near-infrared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 48 publications
(68 reference statements)
2
21
0
Order By: Relevance
“…There are several absorption maxima at shorter wavelengths (e.g., 600-680 nm), which is recognized as wavelength oscillations induced by multilayer interference, including a whole simulated structure of quartz substrate-polymer grating-Au-graphene. [44,46] This is also confirmed by the simulated absorption spectra of Gra-Au NGs with the different Au thickness under the illumination of unpolarized light, as shown in Figure S15, Supporting Information.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…There are several absorption maxima at shorter wavelengths (e.g., 600-680 nm), which is recognized as wavelength oscillations induced by multilayer interference, including a whole simulated structure of quartz substrate-polymer grating-Au-graphene. [44,46] This is also confirmed by the simulated absorption spectra of Gra-Au NGs with the different Au thickness under the illumination of unpolarized light, as shown in Figure S15, Supporting Information.…”
Section: Resultssupporting
confidence: 65%
“…Since the channel sheet resistance of Gra‐Au NGs (see Figure S2b, Supporting Information) is almost 25 times lower than that of photodetector (107 Ω), we consider that the increment of Gra‐Au NGs photodetector resistance is a major contribution of contact resistance at the graphene‐Ag electrode interface, in which the underneath graphene possesses the larger average sheet resistance of 487.8 Ω sq −1 . [ 44 ] The responsivity ( R ) is defined as R = | I ph |/ P , where I ph is the photocurrent at the bias voltage of −1 V, P is the incident light power on the effective area of the photodetector, and the applied laser has a beam spot diameter of 500 µm, which is smaller than the device photosensitive area. Responsivities of these three types of photodetectors at multiple wavelengths are exhibited in Figure 2e, the light power is controlled at 2 mW.…”
Section: Resultsmentioning
confidence: 99%
“…The Raman spectra show the characteristic broad D-, G-, and 2D-peaks for NCG at 1361, 1597, and 2700 cm −1 , respectively. [19,21] Similar to the previous study, where we investigated in detail the graphitization conditions using Raman spectroscopy and X-ray photoelectron spectroscopy (XPS), [19] we employed a fitting technique that involved determining the position of the G-peak and the ratio of the D-mode and G-mode intensities to the hybridization trajectory proposed by Robertson and Ferrari. [23] This analysis confirmed that the NCG film was completely graphitized with nearly 100% sp 2 hybridization, as expected due to similar synthesis conditions.…”
Section: Resultsmentioning
confidence: 99%
“…[67] Device examples of light emission from SCNT have previously been demonstrated which all use traditional metallic electrodes. [68][69][70] However, metallic electrodes induce optical absorption loss and degrade the resonance modes of photonic cavities. [71,72] To overcome these challenges, nanocrystalline graphene electrodes are proposed instead of metallic electrodes.…”
Section: Carbon Nanotube Emittermentioning
confidence: 99%